Sulfobetaine-modified montmorillonite composite material as well as preparation method and application thereof

The sulfobetaine-modified montmorillonite composite material prepared by acidifying montmorillonite and reacting with sulfobetaine solves the problems of poor adsorption capacity and weak anti-interference ability of existing adsorbents, and achieves the effect of efficient adsorption and dispersion, which is suitable for treating antibiotic-contaminated wastewater.

CN119897071AActive Publication Date: 2025-04-29HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510178420.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-29
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The existing modified montmorillonite adsorbents have defects such as poor adsorption capacity, weak anti-interference ability, and easy agglomeration, resulting in high dosage, low adsorption efficiency, poor adaptability, and difficulty in effectively removing antibiotic pollution in the environment.

Method used

By acidizing the montmorillonite and mixing it with the sulfobetaine dispersion, a sulfobetaine-modified montmorillonite composite material was prepared. This method improves the morphological structure and charge distribution of montmorillonite, enhances its adsorption ability to sulfobetaine, and thus improves adsorption performance and dispersion.

Benefits of technology

It has achieved efficient adsorption of organic pollutants, such as antibiotics, which have higher adsorption capacity and adsorption efficiency, strong anti-interference ability, good dispersion and easy separation, and low cost and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897071A_ABST
    Figure CN119897071A_ABST
Patent Text Reader

Abstract

The invention discloses a sulphobetaine-modified montmorillonite composite material and a preparation method and application thereof, the preparation method comprises the following steps: acidifying montmorillonite, reacting the acidified montmorillonite with a sulphobetaine dispersion liquid to obtain the sulphobetaine-modified montmorillonite composite material. Wherein the sulfobetaine contained in the sulfobetaine powder liquid comprises at least one of the following components: 8 parts of sulfobetaine, 10 parts of sulfobetaine, dodecyl dimethyl sulfopropyl betaine, 3-sulfopropyl tetradecyl dimethyl betaine, and 3-sulfopropyl hexadecyl dimethyl betaine. The sulphobetaine-modified montmorillonite composite material prepared by the invention has the advantages of low cost, high adsorption capacity, high adsorption efficiency, strong anti-interference capability, good dispersion, easiness in separation, environmental friendliness and the like, is a novel adsorbent with excellent adsorption performance, and can be widely used for treating organic pollutant wastewater. Organic pollutants in wastewater can be quickly adsorbed and removed on the premise that the dosage is smaller, the use value is high, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmentally friendly adsorption materials and relates to a sulfobetaine-modified montmorillonite composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, various chemicals are continuously produced and used, and emerging organic pollutants continue to enter the environment, generating new environmental risks, with hazards such as strong concealment, difficulty in degradation, carcinogenicity, and reproductive toxicity. Taking antibiotics as an example, doxycycline is an antibiotic. As a new pollutant, it poses a potential threat to both humans and the environment. Doxycycline has a wide range of sources and can enter water bodies through domestic sewage, aquaculture wastewater, pharmaceutical factory wastewater, and medical wastewater, and migrate and transform in the environment. On the one hand, doxycycline inhibits the growth of beneficial microorganisms in water bodies, causing drug-resistant microorganisms to multiply in large numbers and thus destroy the microbial balance of the aquatic ecosystem. At the same time, it has toxic effects on other aquatic organisms, such as freshwater algae and zooplankton, affecting the species richness of aquatic organisms. On the other hand, because doxycycline easily forms chelates with calcium ions and magnesium ions in the environment and is not easily detected in the water phase, the water treatment process may not be able to completely remove this antibiotic, resulting in the risk of long-term low-dose intake of antibiotics. This long-term exposure may cause bacteria in the human body to develop drug resistance, which in turn easily causes serious environmental and health problems. Therefore, it is urgent to remove new pollutants from the environment.

[0003] At present, the methods commonly used to treat new pollutants include biodegradation, advanced oxidation, photodegradation, electrolysis, adsorption, etc. Among them, the adsorption method has attracted widespread attention due to its simple and intuitive operation, diverse types, high treatment efficiency, and good water quality after treatment. However, it also has disadvantages such as limited adsorption capacity, complex regeneration, and possible secondary pollution. Therefore, it is necessary to develop more environmentally friendly, green and efficient adsorbent materials.

[0004] Montmorillonite is widely used as an adsorbent due to its good adsorption performance, natural abundance and low cost. In particular, montmorillonite can be modified by a variety of methods to improve its adsorption performance, thereby expanding its application in the field of new pollutant control. However, in order to make it play a role in daily life, several defects need to be overcome: on the one hand, the adsorption process of montmorillonite takes a long time to reach equilibrium, and the adsorption kinetics are relatively slow, which makes it difficult to cope with sudden water pollution incidents, and its application is limited; on the other hand, the adsorption process of montmorillonite is affected by the impurity content in the water body. These impurities may compete with pollutants for adsorption sites, or change the charge properties of the montmorillonite surface, thereby affecting its adsorption of target pollutants; the existence of the above defects will not only affect the water treatment effect, but also increase the cost of water treatment, greatly limiting the practical application of montmorillonite adsorbents in water treatment. For example, some researchers have proposed a method for modifying montmorillonite using a surfactant (dodecyl betaine or dodecyl sulfobetaine), however, the modified montmorillonite adsorbent obtained therefrom still has the defects of being easily affected by water quality, poor adsorption effect, and easy agglomeration, and excessive surfactants are used in the preparation process, which is not only not conducive to reducing the modification cost, but also easy to cause secondary pollution; in addition, some researchers have proposed a method for modifying acidified sodium-based montmorillonite using hydroxymethyl chitosan, however, the carboxymethyl chitosan modified montmorillonite obtained therefrom still has the defects of poor adsorption capacity and low adsorption efficiency, and it is difficult to achieve efficient adsorption of pollutants under the condition of less dosage. Therefore, obtaining a modified montmorillonite adsorbent with low cost, high adsorption capacity, high adsorption efficiency, strong anti-interference ability, good dispersion and easy separation, and green environmental protection is of great significance for effectively removing antibiotics from wastewater. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a sulfobetaine-modified montmorillonite composite material with low cost, high adsorption capacity, high adsorption efficiency, strong anti-interference ability, good dispersion and easy separation, and green and environmentally friendly, as well as a preparation method and application thereof.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing a sulfobetaine-modified montmorillonite composite material comprises the following steps:

[0008] S1, acidifying the montmorillonite to obtain acidified montmorillonite;

[0009] S2. Mixing the acidified montmorillonite obtained in step S1 with a sulfobetaine dispersion to react, to obtain a sulfobetaine-modified montmorillonite composite material; the sulfobetaine contained in the sulfobetaine dispersion includes at least one of sulfobetaine 8, sulfobetaine 10, dodecyldimethylsulfopropyl betaine, 3-sulfopropyltetradecyldimethyl betaine, and 3-sulfopropylhexadecyldimethyl betaine.

[0010] The above preparation method is further improved, in step S2, the mass ratio of the sulfobetaine contained in the sulfobetaine dispersion to the acidified montmorillonite is 0.05-0.4:1.

[0011] The above preparation method is further improved, in step S2, the sulfobetaine dispersion is prepared by the following method: sulfobetaine is mixed with a solvent, and ultrasonically dispersed at a temperature of 25° C. to 35° C. for 10 min to 30 min to obtain a sulfobetaine dispersion; the concentration of the sulfobetaine dispersion is 0.5 g / L to 4 g / L; and the solvent is ultrapure water.

[0012] The above preparation method is further improved, in step S2, the reaction is carried out under stirring conditions; the reaction temperature is 30°C to 70°C; the stirring speed of the reaction is 300rpm to 500rpm; the stirring time of the reaction is 18h to 30h; after the reaction is completed, the following treatment is also included: the product obtained after the reaction is centrifuged, washed, and dried at a temperature of 70°C for 18h to 30h to obtain a sulfobetaine-modified montmorillonite composite material.

[0013] The above preparation method is further improved, in step S1, montmorillonite is acidified with an acid solution; the mass volume ratio of the montmorillonite to the acid solution is 1g:10mL; the concentration of the acid solution is 1mol / L~2mol / L; the acid solution is a sulfuric acid solution; the montmorillonite is montmorillonite K-10; the montmorillonite also includes the following treatments before use: drying at 50℃~80℃ for 18h~30h; the acidification is carried out at a temperature of 40℃~70℃; the acidification time is 18h~30h; after the acidification is completed, the following treatments are also included: the product obtained after acidification is centrifuged, washed, and dried at a temperature of 70℃ for 18h~30h to obtain acidified montmorillonite.

[0014] As a general technical concept, the present invention also provides a sulfobetaine-modified montmorillonite composite material, which is prepared by the above-mentioned preparation method.

[0015] The above-mentioned sulfobetaine-modified montmorillonite composite material is further improved, wherein the sulfobetaine-modified montmorillonite composite material comprises sulfobetaine and montmorillonite; and the sulfobetaine is loaded on the montmorillonite.

[0016] As a general technical concept, the present invention also provides an application of the above-mentioned sulfobetaine-modified montmorillonite composite material in treating antibiotic wastewater.

[0017] The above application is further improved, comprising the following steps: mixing the sulfobetaine-modified montmorillonite composite material with antibiotic wastewater for adsorption treatment to complete the treatment of the antibiotic wastewater; the addition amount of the sulfobetaine-modified montmorillonite composite material is 0.05g to 0.25g of the sulfobetaine-modified montmorillonite composite material per liter of antibiotic wastewater.

[0018] The above application is further improved, wherein the concentration of the antibiotic in the antibiotic wastewater is 5 mg / L to 25 mg / L; the antibiotic is at least one of doxycycline, tetracycline, ciprofloxacin, and ofloxacin; the pH value of the antibiotic wastewater is 4 to 8; the adsorption treatment is carried out under stirring conditions with a rotation speed of 300 rpm to 500 rpm; the temperature of the adsorption treatment is 15°C to 35°C; and the time of the adsorption treatment is 20 min to 200 min.

[0019] Compared with the prior art, the advantages of the present invention are:

[0020] (1) In view of the shortcomings of existing modified montmorillonite adsorbents, such as poor adsorption capacity, strong anti-interference ability, easy agglomeration, and the resulting defects of high dosage, low adsorption efficiency, and poor adaptability, the present invention creatively proposes a method for preparing a sulfobetaine-modified montmorillonite composite material. The montmorillonite is first acidified, which can not only improve the morphology and structure of the montmorillonite, providing more favorable spatial conditions for the sulfobetaine molecules to enter the montmorillonite interlayer, but also change the charge distribution and properties on the montmorillonite surface, which is conducive to promoting the interaction between the montmorillonite and the sulfobetaine with a zwitterionic structure, and at the same time can destroy the montmorillonite particles. The aggregate structure is conducive to promoting the improvement of the dispersibility of montmorillonite. On this basis, the acidified montmorillonite is mixed with the sulfobetaine dispersion to react, and the sulfobetaine-modified montmorillonite composite material with excellent performance can be prepared by modifying the acidified montmorillonite with sulfobetaine, as follows: on the one hand, by improving the morphology and structure of montmorillonite, the pore size of montmorillonite can be enlarged, and the interlayer spacing of montmorillonite can be increased, so that the sulfobetaine can be more deeply inserted into the interlayer structure of montmorillonite, achieving more sufficient modification, and then better exerting the performance advantages of sulfobetaine, such as improving the hydrophilicity and antistatic property of montmorillonite. At the same time, as the interlayer distance of montmorillonite increases, small pores are generated, the pore size becomes smaller, the pore volume increases, and the proportion of mesoporous structure is increased, which increases the specific surface area to a certain extent, increases the adsorption sites, and improves the adsorption performance; on the other hand, by changing the charge distribution and properties on the surface of montmorillonite, montmorillonite can more effectively attract sulfobetaine molecules through electrostatic attraction, etc., thereby promoting the rapid combination of acidified montmorillonite and sulfobetaine, which can not only promote the effective modification of montmorillonite by sulfobetaine under the condition of less sulfobetaine dosage, making the modification process easier, but also makes the montmorillonite sulfobetaine The bonding between sulfobetaine and sultaine is more firmly established, which is beneficial to improving the structural stability of the material; thirdly, by improving the dispersibility of montmorillonite, montmorillonite can be promoted to absorb more sulfobetaine, so that the montmorillonite particles can contact and react with sulfobetaine more evenly, avoiding the occurrence of excessive or insufficient local modification, thereby ensuring the consistency and uniformity of the modification effect, and improving the quality stability of the modified montmorillonite product. More importantly, by improving the adsorption effect of montmorillonite on sulfobetaine, it is beneficial to promote the uniform dispersion of sulfobetaine on the surface of montmorillonite and form a protective film, which can then be used to prevent the mutual aggregation of montmorillonite particles.Compared with conventional modified montmorillonite adsorbents, the sulfobetaine-modified montmorillonite composite material prepared by the present invention has the following advantages: (a) excellent adsorption performance. By improving the structural morphology of montmorillonite and introducing sulfobetaine, not only the specific surface area and the number of adsorption sites of the composite material can be increased, but also the affinity of the composite material for organic pollutants (such as antibiotics) can be enhanced, so that the sulfobetaine-modified montmorillonite composite material has a higher adsorption capacity and a higher adsorption efficiency, and can more efficiently adsorb organic pollutants under the condition of lower dosage; (b) strong anti-interference ability. By introducing sulfobetaine on the surface of montmorillonite, the surface functional groups of sulfobetaine can be used to make the sulfobetaine-modified montmorillonite composite material have multiple adsorption mechanisms, such as physical adsorption and chemical adsorption. Not only can the surface functional groups of sulfobetaine be used to adjust the pH value of the system so that the composite material can adapt to different pH conditions, but also the surface functional groups of sulfobetaine can be used to interact with the functional groups in organic pollutants to form specific binding, thereby reducing the interference caused by cations and anions in the system, so that the composite material can adapt to the conditions containing (c) good dispersibility and easy separation. The dispersibility of montmorillonite can be improved by acidification, and the agglomeration of montmorillonite can be prevented by forming a sulfobetaine protective film on the surface of montmorillonite, so that the sulfobetaine-modified montmorillonite composite material can be kept in a good dispersion state in the solution, which is conducive to its long-term adsorption in the solution. Solid-liquid separation can be achieved only by standing, which is convenient for recovering the adsorbent; (d) low cost and green environmental protection. The montmorillonite used is abundant in nature, widely distributed, and has a relatively low acquisition cost. It is environmentally friendly. The harm to the environment is small, and the adsorbed montmorillonite can be treated by landfill and other methods. It has good stability and is a low-cost, green and environmentally friendly material. At the same time, the sulfobetaine used as an important amphoteric surfactant has good surface activity, can still maintain good surface activity and solubility in a solution with a high salt concentration, is not easy to produce electrogeneration or phase separation, can remain stable in a wide pH range, and can undergo hydrolysis under certain conditions. It has biodegradability and high environmental friendliness, so it can be used as a corrosion inhibitor and scale inhibitor to form a stable complex with calcium and magnesium ions in water. In addition, in the preparation method of the present invention, a sulfobetaine-modified montmorillonite composite material with excellent performance can be prepared under the condition of less sulfobetaine usage, which is conducive to reducing the preparation cost. The sulfobetaine-modified montmorillonite composite material prepared by the present invention has the advantages of low cost, high adsorption capacity, high adsorption efficiency, strong anti-interference ability, good dispersion and easy separation, green environmental protection, etc. It is a new adsorbent with excellent adsorption performance, can be widely used in treating organic pollutant wastewater, can quickly adsorb and remove organic pollutants in wastewater with less usage, has high use value and good application prospects.

[0021] (2) In the preparation method of the present invention, sulfuric acid solution is used as the acid solution to acidify montmorillonite. The chemical environment of the surface and interlayer of the prepared acidified montmorillonite is more conducive to subsequent modification treatment. It can also facilitate further reaction with organic reagents, etc., to achieve further optimization and customization of the performance of montmorillonite to meet the special needs of different application fields, which is not available in other acid solutions.

[0022] (3) The present invention also provides an application of a sulfobetaine-modified montmorillonite composite material in treating antibiotic wastewater. Specifically, the sulfobetaine-modified montmorillonite composite material is mixed with antibiotic wastewater for adsorption treatment. The antibiotics in the wastewater can be efficiently adsorbed by stirring. The composite material has the advantages of good adsorption effect, high adsorption efficiency, simple operation, low cost, and easy separation after adsorption. The composite material can effectively remove antibiotics from the wastewater, which is of great significance for the effective purification of antibiotic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0024] Figure 1 The scanning electron microscope images are of the sulfobetaine 8-modified montmorillonite composite material (AM8) and the original montmorillonite (CK) prepared in Example 1 of the present invention.

[0025] Figure 2 It is a Fourier transform infrared spectrum of the sulfobetaine-modified montmorillonite composite materials (AM8, AM10, AM12, AM14, AM16) prepared in Example 1 of the present invention.

[0026] Figure 3 This is a comparison chart of the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 2 of the present invention at different KCl ion strengths.

[0027] Figure 4 This is a comparison chart of the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 2 of the present invention under different NaCl ion strengths.

[0028] Figure 5 This is a comparison chart of the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 3 of the present invention under different pH conditions.

[0029] Figure 6 This is a diagram showing the adsorption effect of different types of antibiotics on the sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 4 of the present invention.

[0030] Figure 7 This is a comparison chart of the adsorption effects of sulfobetaine-modified montmorillonite composite materials (AM8, AM10, AM12, AM14, AM16) and sulfobetaine-montmorillonite composite materials (M8, M10, M12, M14, M16) on doxycycline in Example 5 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0032] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values ​​of more than three repeated experiments.

[0033] Example 1

[0034] A method for preparing a sulfobetaine-modified montmorillonite composite material, specifically comprising: modifying acidified montmorillonite using sulfobetaine 8, comprising the following steps:

[0035] (1) Put K-10 montmorillonite into an oven and dry it at 70°C for 24 hours to obtain dry montmorillonite, which is recorded as CK.

[0036] (2) 10 g of dry montmorillonite was placed in 100 mL of 1 mol / L sulfuric acid solution and mechanically stirred at 40°C for 24 h. The mixture was then centrifuged and washed, the supernatant was discarded, and the precipitate was placed in an oven and dried at 70°C for 24 h, and then collected and stored to obtain acidified montmorillonite.

[0037] (3) 0.1 g of sulfobetaine 8 was ultrasonically dispersed in 100 mL of ultrapure water at 25° C. for 10 min to obtain a sulfobetaine 8 dispersion.

[0038] (4) 1 g of the acidified montmorillonite obtained in step (2) was placed in the sulfobetaine 8 dispersion obtained in step (3), mechanically stirred at 40° C. and 500 rpm for 24 h, centrifuged, washed with deionized water and ethanol until the supernatant was clear, and dried at 70° C. for 24 h to obtain a sulfobetaine 8-modified montmorillonite composite material, recorded as AM8.

[0039] In this embodiment, different types of sulfobetaine are also used to prepare sulfobetaine-modified montmorillonite composite materials, which are basically the same as Example 1, except that sulfobetaine 10, dodecyldimethyl sulfopropyl betaine, 3-sulfopropyltetradecyldimethyl betaine, and 3-sulfopropylhexadecyldimethyl betaine are used instead of sulfobetaine 8, wherein when the sulfobetaine is sulfobetaine 10, dodecyldimethyl sulfopropyl betaine, 3-sulfopropyltetradecyldimethyl betaine, and 3-sulfopropylhexadecyldimethyl betaine, they are sulfobetaine 10-modified montmorillonite composite materials, dodecyldimethyl sulfopropyl betaine-modified montmorillonite composite materials, 3-sulfopropyltetradecyldimethyl betaine-modified montmorillonite composite materials, and 3-sulfopropylhexadecyldimethyl betaine-modified montmorillonite composite materials, and are recorded as AM10, AM12, AM14, and AM16, respectively.

[0040] In this embodiment, different types of sulfobetaine are also used to prepare sulfobetaine-montmorillonite composite materials, which are basically the same as Example 1, except that sulfobetaine 8, sulfobetaine 10, dodecyl dimethyl sulfopropyl betaine, 3-sulfopropyl tetradecyl dimethyl betaine, and 3-sulfopropyl hexadecyl dimethyl betaine are used as sulfobetaine, and dry montmorillonite (unacidified) is used instead of acidified montmorillonite, wherein when the sulfobetaine is sulfobetaine 8, sulfobetaine 10, dodecyl dimethyl sulfopropyl betaine, 3-sulfopropyl tetradecyl dimethyl betaine, and 3-sulfopropyl hexadecyl dimethyl betaine, the sulfobetaine is sulfobetaine 8, sulfobetaine 10, dodecyl dimethyl sulfopropyl betaine, 3-sulfopropyl tetradecyl dimethyl betaine, and 3-sulfopropyl hexadecyl dimethyl betaine. When methyl sulfopropyl betaine, 3-sulfopropyl tetradecyl dimethyl betaine and 3-sulfopropyl hexadecyl dimethyl betaine, they are sulfobetaine 8-montmorillonite composite material, sulfobetaine 10-montmorillonite composite material, dodecyl dimethyl sulfopropyl betaine-montmorillonite composite material, 3-sulfopropyl tetradecyl dimethyl betaine-montmorillonite composite material and 3-sulfopropyl hexadecyl dimethyl betaine-montmorillonite composite material, and are recorded as M8, M10, M12, M14 and M16 respectively.

[0041] Figure 1 The scanning electron microscope images are of the sulfobetaine 8-modified montmorillonite composite material (AM8) and the original montmorillonite (CK) prepared in Example 1 of the present invention. Figure 1 In this figure, (a) and (b) are CK, (c) and (d) are AM8. Figure 1 (a) and (b) show that the montmorillonite before modification has a flat surface structure, a smooth surface, and a clear layered structure. Figure 1 (c) It can be seen that after modification with sulfobetaine 8, the montmorillonite crystal layer has obvious curling; Figure 1 (d) It can be seen that after acid activation and surfactant modification, montmorillonite is composed of a large number of broken crystal layers, which are in a loose flaky aggregation state and have irregular curling or wrinkling structures on the surface.

[0042] In order to verify whether the introduction of sulfobetaine improves the dispersibility of montmorillonite, the present invention detects the N 2 Adsorption-desorption isotherms, the specific surface area, pore size, pore volume and other corresponding parameters of sulfobetaine 8-acidified montmorillonite and dry montmorillonite were calculated according to the Barrete-Joynere-Halenda model, as shown in Table 1. As can be seen from Table 1, compared with dry montmorillonite, the specific surface area of ​​sulfobetaine 8-acidified montmorillonite increases, which indicates that the addition of sulfobetaine can improve the agglomeration of montmorillonite and expand the specific surface area.

[0043] Table 1 Specific surface area, pore size and pore volume of sulfobetaine 8-modified montmorillonite and original montmorillonite

[0044] <![CDATA[BET specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) AM8 90.8061 0.154440 6.5727 CK 51.8665 0.125500 8.6214

[0045] Figure 2 The following is a Fourier transform infrared spectrum of the sulfobetaine-modified montmorillonite composite materials (AM8, AM10, AM12, AM14, AM16) prepared in Example 1 of the present invention. Figure 2 It can be seen that compared with the unmodified montmorillonite, the sulfobetaine-modified montmorillonite composite material prepared in the present invention has a plurality of peaks related to sulfobetaine, indicating that sulfobetaine is loaded on the montmorillonite.

[0046] Example 2

[0047] The anti-interference ability of sulfobetaine-modified montmorillonite composite materials in treating antibiotic wastewater was investigated. Specifically, sulfobetaine-modified montmorillonite composite materials were used to adsorb doxycycline wastewater, including the following steps:

[0048] Group 1: Take 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1, add it to a solution with a KCl concentration of 5 mg / L and a doxycycline concentration of 5 mg / L (the volume of the solution is 100 mL, and the pH value is 6.8), and place it at 25°C and 400 rpm for mechanical stirring and adsorption for 2 hours to complete the treatment of doxycycline wastewater.

[0049] The second group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a solution with a KCl concentration of 10 mg / L and a doxycycline concentration of 5 mg / L (the volume of the solution was 100 mL and the pH value was 6.8), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of doxycycline wastewater.

[0050] The third group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a solution with a KCl concentration of 15 mg / L and a doxycycline concentration of 5 mg / L (the volume of the solution was 100 mL and the pH value was 6.8), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of doxycycline wastewater.

[0051] Group 4: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a solution with a KCl concentration of 20 mg / L and a doxycycline concentration of 5 mg / L (the volume of the solution was 100 mL and the pH value was 6.8), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 h to complete the treatment of doxycycline wastewater.

[0052] Group 5: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a solution with a KCl concentration of 25 mg / L and a doxycycline concentration of 5 mg / L (the volume of the solution was 100 mL, and the pH value was 6.8), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 h to complete the treatment of doxycycline wastewater.

[0053] After the mechanical stirring adsorption was completed, 1 mL of the treated solution was taken and the doxycycline content was determined by high performance liquid chromatography.

[0054] Figure 3 This is a comparison chart of the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 2 of the present invention at different KCl ion strengths. Figure 3 It can be seen that the concentrations of potassium chloride added to the wastewater are 5 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, and 25 mg / L, and the corresponding removal rates of doxycycline are 97.76%, 98.26%, 98.47%, 97.42%, and 98.08%, respectively. It can be seen that adding potassium chloride to wastewater does not affect the adsorption effect of sulfobetaine 8-modified montmorillonite composite material (AM8) on doxycycline, and with the increase of KCl concentration, the adsorption of doxycycline by sulfobetaine 8-modified montmorillonite composite material (AM8) maintains a good effect without obvious change. This phenomenon confirms that there is chemical adsorption in the adsorption of doxycycline by sulfobetaine 8-modified montmorillonite composite material (AM8), and the adsorption site reacts with the specific functional group on the doxycycline molecule. KCl will not interfere with this specific chemical binding, and the KCl concentration will not have a significant effect on the adsorption.

[0055] In this example, the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) at different KCl ion strengths was also investigated, which was basically the same as Example 2, except that KCl was used instead of NaCl.

[0056] Figure 4 This is a comparison chart of the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 2 of the present invention at different NaCl ion strengths. Figure 4 It can be seen that the addition of sodium chloride in wastewater does not affect the adsorption effect of sulfobetaine 8-modified montmorillonite composite material (AM8) on doxycycline, and with the increase of NaCl concentration, the adsorption of doxycycline by sulfobetaine 8-modified montmorillonite composite material (AM8) remains good without significant change. Figure 3 Similar. In addition, Figure 4 It can be seen that when the addition amount of sulfobetaine 8-modified montmorillonite composite material (AM8) is 10 mg / 100 mL, after 20 min of adsorption treatment, the removal rates of doxycycline in doxycycline wastewater with sodium chloride concentrations of 5 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, and 25 mg / L are 80.06%, 84.05%, 86.28%, 92.35%, and 79.24%, respectively. It can be seen that when the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared by the present invention is used to treat antibiotic wastewater, it can efficiently remove antibiotics in wastewater under the premise of using less amount.

[0057] Depend on Figure 3 and Figure 4 It can be seen from the results in that the sulfobetaine-modified montmorillonite composite material prepared by the present invention exhibits very excellent anti-interference ability.

[0058] Example 3

[0059] The adaptability of sulfobetaine-modified montmorillonite composite materials in treating antibiotic wastewater with different pH values ​​was investigated. Specifically, sulfobetaine-modified montmorillonite composite materials were used to adsorb doxycycline wastewater with different pH values, including the following steps:

[0060] Group 1: Take 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1, add it to a doxycycline solution with a pH of 3 and a concentration of 5 mg / L (the volume of the solution is 100 mL), place it at 25°C and 400 rpm for mechanical stirring and adsorption for 2 hours, and complete the treatment of doxycycline wastewater.

[0061] The second group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a doxycycline solution (the volume of the solution was 100 mL) with a pH of 5 and a concentration of 5 mg / L, and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of doxycycline wastewater.

[0062] The third group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a doxycycline solution (the volume of the solution was 100 mL) with a pH of 7 and a concentration of 5 mg / L, and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of doxycycline wastewater.

[0063] Group 4: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a doxycycline solution (the volume of the solution was 100 mL) with a pH of 9 and a concentration of 5 mg / L, and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 h to complete the treatment of doxycycline wastewater.

[0064] Group 5: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a doxycycline solution (the volume of the solution was 100 mL) with a pH of 11 and a concentration of 5 mg / L, and mechanically stirred and adsorbed at 25° C. and 400 rpm for 2 h to complete the treatment of doxycycline wastewater.

[0065] After the mechanical stirring adsorption was completed, 1 mL of the treated solution was taken and the doxycycline content was determined by high performance liquid chromatography.

[0066] Figure 5 It is a comparison diagram of the adsorption effect of doxycycline on the sulfobetaine 8-modified montmorillonite composite material (AM8) under different pH conditions in Example 3 of the present invention. As shown in Figure 5, when the pH is 3-9, the sulfobetaine 8-modified montmorillonite maintains a high adsorption rate for doxycycline. In an acidic environment, the amino group on doxycycline is protonated and positively charged, and at this time, the surface of the sulfobetaine 8-modified montmorillonite composite material (AM8) is negatively charged, so the adsorption efficiency is improved by electrostatic attraction. However, as the pH increases, the negative charge on the surface of the sulfobetaine 8-modified montmorillonite composite material (AM8) increases, and the doxycycline molecule also presents a negative charge, which leads to a decrease in the adsorption effect. It can be seen that there is a strong electrostatic attraction between the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared by the present invention and doxycycline. At the same time, when the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared by the present invention is used to treat antibiotic wastewater, it shows very excellent adsorption capacity for antibiotic wastewater with a pH value of 3-9, and has good adaptability to water bodies with different pH values.

[0067] Example 4

[0068] The invention discloses an application of a sulfobetaine-modified montmorillonite composite material in treating antibiotic wastewater, specifically using the sulfobetaine-modified montmorillonite composite material to perform adsorption treatment on doxycycline (DCH) wastewater, tetracycline (TC) wastewater, ofloxacin (OF) wastewater, ciprofloxacin (CIP) wastewater, and norfloxacin (NOR) wastewater, respectively, comprising the following steps:

[0069] Group 1: Take 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1, add it to a doxycycline (DCH) solution with a concentration of 5 mg / L (the volume of the solution is 100 mL, and the pH value is 6.8), and place it at 25°C and 400 rpm for mechanical stirring and adsorption for 2 hours to complete the treatment of the wastewater.

[0070] The second group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a 5 mg / L tetracycline (TC) solution (the volume of the solution was 100 mL, and the pH value was 6.4), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of the wastewater.

[0071] The third group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a 5 mg / L ofloxacin (OF) solution (the volume of the solution was 100 mL, and the pH value was 6.7), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of the wastewater.

[0072] The fourth group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a 5 mg / L ciprofloxacin (CIP) solution (the volume of the solution was 100 mL, and the pH value was 7.1), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 h to complete the treatment of the wastewater.

[0073] The fifth group: 10 mg of the sulfobetaine 8-modified montmorillonite composite material (AM8) prepared in Example 1 was added to a 5 mg / L norfloxacin (NOR) solution (the volume of the solution was 100 mL, and the pH value was 5.9), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 h to complete the treatment of the wastewater.

[0074] After the mechanical stirring adsorption was completed, 1 mL of the treated solution was taken and the antibiotic content in the wastewater was determined by high performance liquid chromatography.

[0075] Figure 6 The figure is the adsorption effect diagram of different types of antibiotics by sulfobetaine 8-modified montmorillonite composite material (AM8) in Example 4 of the present invention. As shown in Figure 6, the removal rates of doxycycline (DCH), tetracycline (TC), ofloxacin (OF), ciprofloxacin (CIP) and norfloxacin (NOR) in wastewater prepared by sulfobetaine 8-modified montmorillonite composite material (AM8) after 2 hours of treatment are 98.47%, 98.85%, 96.65%, 98.03% and 97.35% respectively. It can be seen that the sulfobetaine-modified montmorillonite composite material prepared by the present invention has a good adsorption effect on different types of antibiotics, can effectively remove antibiotics in water bodies, and can further achieve effective purification of antibiotic wastewater, which shows that the sulfobetaine-modified montmorillonite composite material of the present invention can be widely used in the purification of different water bodies such as rivers, lakes and groundwater, has high use value and good application prospects, and is of great significance for improving water quality and protecting water ecosystems.

[0076] Example 5

[0077] A sulfobetaine-modified montmorillonite composite material is used in treating antibiotic wastewater, specifically using the sulfobetaine-modified montmorillonite composite material to adsorb doxycycline (DCH) wastewater, comprising the following steps:

[0078] Group 1: Take 5 mg of the sulfobetaine-modified montmorillonite composite materials (AM8, AM10, AM12, AM14, AM16) prepared in Example 1, add them into a doxycycline (DCH) solution with a concentration of 10 mg / L (the volume of the solution is 100 mL, and the pH value is 6.8), place them at 25°C and 400 rpm for mechanical stirring and adsorption for 2 hours to complete the treatment of the wastewater.

[0079] The second group: 5 mg of the sulfobetaine-montmorillonite composite materials (M8, M10, M12, M14, M16) prepared in Example 1 were added to a doxycycline (DCH) solution with a concentration of 10 mg / L (the volume of the solution was 100 mL, and the pH value was 6.8), and mechanically stirred and adsorbed at 25°C and 400 rpm for 2 hours to complete the treatment of the wastewater.

[0080] After the mechanical stirring adsorption was completed, 1 mL of the treated solution was taken and the doxycycline content was determined by high performance liquid chromatography.

[0081] Figure 7 This is a comparison chart of the adsorption effect of sulfobetaine-modified montmorillonite composite materials (AM8, AM10, AM12, AM14, AM16) and sulfobetaine-montmorillonite composite materials (M8, M10, M12, M14, M16) on doxycycline in Example 5 of the present invention. Figure 7 It can be seen that the removal rates of doxycycline by sulfobetaine-modified montmorillonite composite materials (AM8, AM10, AM12, AM14, AM16) after stirring and adsorbing for 2 hours were 70.02%, 63.74%, 67.81%, 59.91%, and 44.33%, respectively. Under the same conditions, the removal rates of doxycycline by sulfobetaine-montmorillonite composite materials (M8, M10, M12, M14, M16) were 44.37%, 29.68%, 44.40%, 22.94%, and 34.73%, respectively. It can be seen that acidification of montmorillonite is beneficial to improve the adsorption performance of sulfobetaine-modified montmorillonite composite materials. The reasons may be: on the one hand, after acidification, the introduction of hydrogen ions can change the charge properties of the montmorillonite surface and enhance the adsorption of polar molecules or ions; on the other hand, proper acidification can expand the pore size of montmorillonite, so that it can accommodate larger molecules, thereby improving the adsorption capacity of macromolecular pollutants such as organic matter. In addition, acidification can reduce the agglomeration phenomenon between montmorillonite particles, thereby improving its dispersion stability in the system and improving the performance of the composite material.

[0082] It can be seen from the above results that, compared with conventional modified montmorillonite adsorbents, the sulfobetaine-modified montmorillonite composite material prepared by the present invention has the following advantages: (a) excellent adsorption performance. By improving the structural morphology of montmorillonite and introducing sulfobetaine, not only the specific surface area and the number of adsorption sites of the composite material can be increased, but also the affinity of the composite material for organic pollutants (such as antibiotics) can be enhanced, so that the sulfobetaine-modified montmorillonite composite material has a higher adsorption capacity and a higher adsorption efficiency, and can more efficiently adsorb organic pollutants at a lower dosage; (b) anti-interference The ability is strong. By introducing sulfobetaine on the surface of montmorillonite, the surface functional groups contained in sulfobetaine can be used to make the sulfobetaine-modified montmorillonite composite material have a variety of adsorption mechanisms, such as physical adsorption and chemical adsorption. Not only can the surface functional groups contained in sulfobetaine be used to adjust the pH value of the system so that the composite material can adapt to different pH conditions, but also the surface functional groups contained in sulfobetaine can be used to interact with the functional groups in organic pollutants and specifically bind to them, thereby reducing the interference caused by the cations and anions in the system, so that the composite material can (c) Good dispersibility and easy separation. The dispersibility of montmorillonite can be improved by acidification, and the agglomeration of montmorillonite can be prevented by forming a sulfobetaine protective film on the surface of montmorillonite. Therefore, the sulfobetaine-modified montmorillonite composite material can be kept in a good dispersion state in the solution, which is conducive to its long-term adsorption in the solution. Solid-liquid separation can be achieved only by standing, which is convenient for recovering the adsorbent. (d) Low cost and green environmental protection. The montmorillonite used is abundant in nature, widely distributed, and has a relatively low acquisition cost. The harm to the environment is small, and the adsorbed montmorillonite can be treated by landfill and other methods. It has good stability and is a low-cost, green and environmentally friendly material. At the same time, the sulfobetaine used as an important amphoteric surfactant has good surface activity, can still maintain good surface activity and solubility in a solution with a high salt concentration, is not easy to produce electricity generation or phase separation, can remain stable in a wide pH range, and can undergo hydrolysis under certain conditions. It has biodegradability and high environmental friendliness, so it can be used as a corrosion inhibitor and scale inhibitor to form a stable complex with calcium and magnesium ions in water. In addition, in the preparation method of the present invention, a sulfobetaine-modified montmorillonite composite material with excellent performance can be prepared under the condition of less sulfobetaine usage, which is conducive to reducing the preparation cost. Therefore, the sulfobetaine-modified montmorillonite composite material prepared by the present invention has the advantages of low cost, high adsorption capacity, high adsorption efficiency, strong anti-interference ability, good dispersion and easy separation, green environmental protection, etc. It is a new adsorbent with excellent adsorption performance, can be widely used in treating organic pollutant wastewater, can quickly adsorb and remove organic pollutants in wastewater with less usage, has high use value and good application prospects.

[0083] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a sulfobetaine-modified montmorillonite composite material, characterized in that: The following steps are involved: S1, acidifying the montmorillonite to obtain acidified montmorillonite; S2. Mixing the acidified montmorillonite obtained in step S1 with a sulfobetaine dispersion to react, to obtain a sulfobetaine-modified montmorillonite composite material; the sulfobetaine contained in the sulfobetaine dispersion includes at least one of sulfobetaine 8, sulfobetaine 10, dodecyldimethylsulfopropyl betaine, 3-sulfopropyltetradecyldimethyl betaine, and 3-sulfopropylhexadecyldimethyl betaine.

2. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the sulfobetaine contained in the sulfobetaine dispersion to the acidified montmorillonite is 0.05-0.4:

1.

3. The preparation method according to claim 2, characterized in that: In step S2, the sulfobetaine dispersion is prepared by the following method: sulfobetaine is mixed with a solvent, and ultrasonically dispersed at a temperature of 25° C. to 35° C. for 10 min to 30 min to obtain a sulfobetaine dispersion; the concentration of the sulfobetaine dispersion is 0.5 g / L to 4 g / L; and the solvent is ultrapure water.

4. The preparation method according to claim 1, characterized in that: In step S2, the reaction is carried out under stirring conditions; the reaction temperature is 30°C to 70°C; the stirring speed of the reaction is 300rpm to 500rpm; the stirring time of the reaction is 18h to 30h; after the reaction is completed, the following treatment is also included: the product obtained after the reaction is centrifuged, washed, and dried at a temperature of 70°C for 18h to 30h to obtain a sulfobetaine-modified montmorillonite composite material.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S1, the montmorillonite is acidified with an acid solution; the mass volume ratio of the montmorillonite to the acid solution is 1g:10mL; the concentration of the acid solution is 1mol / L-2mol / L; the acid solution is a sulfuric acid solution; the montmorillonite is montmorillonite K-10; the montmorillonite also includes the following treatments before use: drying at 50°C-80°C for 18h-30h; the acidification is performed at a temperature of 40°C-70°C; the acidification time is 18h-30h; after the acidification is completed, the following treatments are also included: the product obtained after the acidification is centrifuged, washed, and dried at a temperature of 70°C for 18h-30h to obtain the acidified montmorillonite.

6. A sulfobetaine-modified montmorillonite composite material, characterized in that: The sulfobetaine-modified montmorillonite composite material is prepared by the preparation method described in any one of claims 1 to 5.

7. The sulfobetaine-modified montmorillonite composite material according to claim 6, characterized in that: The sulfobetaine-modified montmorillonite composite material comprises sulfobetaine and montmorillonite; the sulfobetaine is loaded on the montmorillonite.

8. Use of the sulfobetaine-modified montmorillonite composite material as claimed in claim 6 or 7 in treating antibiotic wastewater.

9. The use according to claim 8, characterized in that: The following steps are involved: The sulfobetaine-modified montmorillonite composite material is mixed with antibiotic wastewater for adsorption treatment to complete the treatment of the antibiotic wastewater; the addition amount of the sulfobetaine-modified montmorillonite composite material is 0.05g to 0.25g per liter of antibiotic wastewater.

10. The use according to claim 9, characterized in that: The concentration of the antibiotic in the antibiotic wastewater is 5 mg / L to 25 mg / L; the antibiotic is at least one of doxycycline, tetracycline, ciprofloxacin, and ofloxacin; the pH value of the antibiotic wastewater is 4 to 8; the adsorption treatment is carried out under stirring conditions with a rotation speed of 300 rpm to 500 rpm; the temperature of the adsorption treatment is 15° C. to 35° C.; and the time of the adsorption treatment is 20 min to 200 min.

Citation Information

Patent Citations

  • Modified montmorillonite capable of adsorbing zearalenone and method for preparing montmorillonite

    CN102658081A